GROWTH AND PRODUCTION OF SWEET CORN (Zea mays saccharata Sturt.) THROUGH ORGANIC AND INORGANIC FERTILIZATION: GROWTH AND PRODUCTION OF SWEET CORN (Zea mays saccharata Sturt.) THROUGH ORGANIC AND INORGANIC FERTILIZATION - Sanniwati Saragih, Wismaroh (LPPM UPMI, 2023)
Sweet corn (Zea mays saccharata Sturt.) is a horticultural product that is widely consumed as a vegetable or consumed directly by Indonesian people because it has a sweeter taste than ordinary corn. Corn plants require sufficient nutrients to be able to grow and produce optimally, so fertilization is a determining factor for the success of corn cultivation. This research was carried out in the Experimental Garden of the Faculty of Agriculture, Indonesian Community Development University (UPMI), Medan, from July to September 2022. A factorial randomized block design (RAK) with two treatment factors for organic fertilizer treatment, namely: K0 = Control; K1 = 1 kg/plot; K2 = 1.5 kg/plot; K3 = 2 kg/plot, and inorganic fertilizer treatment, namely: U0 = Control; U1 = 50 g/plot; U2 = 100 g/plot; U3 = 150 g/plot, repeated four times. Parameters observed were (1) plant height (cm), (2) number of leaves (strands), (3) cob length (cm), and (4) cob weight (g). The results of the research on organic fertilizer treatment had no significant effect on the observed parameters. But the application of inorganic fertilizers had a significant effect on plant height but had no effect on the number of leaves observed, cob length, or cob weight of sweet corn. The combination of organic and inorganic fertilizers for growth and production was better than the control treatment or the treatment of organic and inorganic fertilizers.